Chartarlactams Q−T, Dimeric Phenylspirodrimanes with Antibacterial and Antiviral Activities. Issue 6 (8th June 2020) - Liu, Dong; Li, Yong; Guo, Xingchen; Ji, Wei; Lin, Wenhan
Abstract: Four new phenylspirodrimane‐type dimers, namely chartarlactams Q−T, along with stachyin B were isolated from the fermentation broth of a sponge‐derived fungus Stachybotrys chartarum WGC‐25 C‐6. Chartarlactams Q−T were structurally featured by the dimerization of two units of phenylspirodrimane linked by a C−N bond. Their structures were determined on the basis of extensive spectroscopic analysis, while quantum ECD calculation and modified Mosher's method were used for the assignment of absolute configurations. Chartarlactams Q−S and stachyin B showed moderate inhibition against bacterial pathogen Staphylococcus aureus with MIC values ranging from 4 μg/mL to 16 μg/mL, and chartarlactam T exhibited significant inhibition toward ZIKV virus. Abstract :